Script analysis for theatre tools for interpretation, collaboration and production - Knopf, Robert 1961- (Bloomsbury Methuen Drama, 2017)
"Provides theater students and emerging theater artists with the tools, skills and a shared language to analyze play scripts, communicate about them and collaborate with others on stage productions...Readers will learn to distinguish the big picture of a script, dissect and 'score' smaller units and moment-to-moment action and create individualized blueprints from which to collaborate on shaping the action in production from their perspectives as actors, directors and designers."